Indonesian migrant workers activism in Hong Kong - ANJANI TRI FATHARINI (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: The article explains why the Indonesian Migrant Workers Alliance (JBMI) has a chance of succeeding in Hong Kong. The JBMI is intriguing because it is the largest alliance of Indonesian migrant workers and consists of a confederation of separate organizations speaking with one voice.Method: Methodologically, this study employs a qualitative strategy predicated on primer data. Primary data was gathered through in-depth interviews with a sample of politically active Indonesian migrant workers. Using the theory of political opportunity structures, this article explains why JBMI can thrive in Hong Kong.Findings: Two factors make Hong Kong an ideal setting for the growth of JBMI: (1) the hybrid regime’s characteristics allow for collective actions by creating expansive political spaces for migrant workers, and (2) Indonesian migrant workers in Hong Kong have the awareness necessary to effectively manage the city’s resources.Implications/Novel Contribution: This research hopes to add to what is already known about Indonesian migrant workers, especially in the self-organizing migrants’ movement. We hope to demonstrate the strength of vulnerable migrant domestic workers through this study.